2015
DOI: 10.1155/2015/924539
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gender on the Association of Epicardial Fat Thickness, Obesity, and Circadian Blood Pressure Pattern in Hypertensive Patients

Abstract: This study aimed to investigate the effects of gender on the association between epicardial fat thickness (EFT) and circadian blood pressure (BP) changes in patients with recently diagnosed essential hypertension (EH). A total of 441 patients with EH (male/female: 236/205, mean age: 50.7 ± 13.8) and 83 control patients underwent 24-hour ambulatory BP monitoring and echocardiography. Obese EH patients had higher circadian BP profile with BP variability, wall thickness, and left ventricular mass than nonobese EH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
1
21
1
Order By: Relevance
“…Left atrial volume was measured by prolate ellipse methods. Echocardiographic assessments of EFT, defined as the echo-free space between the outer wall of the myocardium and the visceral layer of the pericardium, were measured perpendicularly from the free wall of the right ventricle at end-systole in three cardiac cycles as previously described 4). Because one of the critical issues in EFT measurement is the inconsistency in measurement location, the mean EFT was averaged from images of the parasternal long axis, parasternal short axis, and apical 4-chamber view.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Left atrial volume was measured by prolate ellipse methods. Echocardiographic assessments of EFT, defined as the echo-free space between the outer wall of the myocardium and the visceral layer of the pericardium, were measured perpendicularly from the free wall of the right ventricle at end-systole in three cardiac cycles as previously described 4). Because one of the critical issues in EFT measurement is the inconsistency in measurement location, the mean EFT was averaged from images of the parasternal long axis, parasternal short axis, and apical 4-chamber view.…”
Section: Methodsmentioning
confidence: 99%
“…Although the association between intra-abdominal fat and CV risk has been well-studied, epicardial fat tissue is a newly identified CV risk factor that reflects visceral adiposity 3). There is an association between epicardial adipose tissue and hypertension, and echocardiographic epicardial fat thickness (EFT) is increased in the non-dipper pattern 4)5)…”
Section: Introductionmentioning
confidence: 99%
“…Echocardiographic assessments of EFT, defined as the echo-free space between the outer wall of the myocardium and the visceral layer of the pericardium, were measured perpendicularly from the free wall of the right ventricle at the end-systole in three cardiac cycles according to the method we previously described (Fig. 1 ) [ 20 ]. Because one of the critical issues in EFT measurement is the inconsistency in the measurement location, and mean EFT was averaged from the images of the parasternal long axis, parasternal short axis and apical 4 chamber view.…”
Section: Methodsmentioning
confidence: 99%
“…EF differs from other fat depots (omental, visceral/abdominal, or subcutaneous) by having significantly larger number of smaller adipocytes, a different fatty acid and protein composition, as well as different lipid metabolism (increased fatty acid synthesis and fatty acid breakdown) [17]. Several recent human studies have shown an association between obesity and increases in EF mass [37, 38]. Clinical studies have also shown that EF expresses increased inflammatory cytokines (TNFα and IL6) compared to other adipose depots in patients with coronary artery disease and other diseases [2, 18].…”
Section: Introductionmentioning
confidence: 99%